Food habits of the Harpy Eagle, a top predator from the Amazonian rainforest canopy - Aguiar-Silva, Francisca Helena (Journal of Raptor Research, 2020)
The Harpy Eagle (Harpia harpyja), the heaviest and the most powerful bird of prey in the canopy of the Neotropical rainforests, is critically endangered in some parts of its range, mainly due to hunting pressure and habitat loss by deforestation. In this study, we found that the diet of five breeding pairs of Harpy Eagles in the central Amazonian rainforest over three years was dominated by two species of sloths (Bradypus variegatus and Choloepus didactylus) in terms of number of individuals and biomass consumed. Twelve other species, including primates, rodents, carnivores, and birds, also contributed to the Harpy Eagle diet in central Amazonia; there was no evidence of Harpy Eagle predation on livestock or domestic animals. Throughout the Harpy Eagle's entire range, 69 prey species have been documented, indicating that it can use a wide range of food resources. However, in our study, there was an evident diet specialization, resulting in a niche breadth which was relatively low (Bsta = 0.171). Conservation of Harpy Eagles should include protection of nesting trees, territories, and prey species to maintain the variability and availability of resources and its ecological functions throughout its geographic range. © The Raptor Research Foundation, Inc.